En bloc and segmental deletions of human XIST reveal X chromosome inactivation-involving RNA elements. Issue 8 (20th February 2019) - Lee, Hyeon J; Gopalappa, Ramu; Sunwoo, Hongjae; Choi, Seo-Won; Ramakrishna, Suresh; Lee, Jeannie T; Kim, Hyongbum H; Nam, Jin-Wu
Abstract: The XIST RNA is a non-coding RNA that induces X chromosome inactivation (XCI). Unlike the mouse Xist RNA, how the human XIST RNA controls XCI in female cells is less well characterized, and its functional motifs remain unclear. To systematically decipher the XCI-involving elements of XIST RNA, 11 smaller XIST segments, including repeats A, D and E; human-specific repeat elements; the promoter; and non-repetitive exons, as well as the entire XIST gene, were homozygously deleted in K562 cells using the Cas9 nuclease and paired guide RNAs at high efficiencies, followed by high-throughput RNA sequencing and RNA fluorescence in situ hybridization experiments. Clones containing en bloc and promoter deletions that consistently displayed no XIST RNAs and a global up-regulation of X-linked genes confirmed that the deletion of XIST reactivates the inactive X chromosome. Systematic analyses of segmental deletions delineated that exon 5 harboring the non-repeat element is important for X-inactivation maintenance, whereas exons 2, 3 and 4 as well as the other repeats in exon 1 are less important, a different situation from that of mouse Xist . This Cas9-assisted dissection of XIST allowed us to understand the unique functional domains within the human XIST RNA.